Microencapsulation of L. acidophilus NRRL B-4495 in whey Protein-Pullulan Microparticles: Influence of Pullulan Concentration and Outlet Temperature - Çabuk, Burcu; Tellioglu Harsa, Sebnem (Journal of Nutritional Therapeutics, 2016)
Spray drying technique is one of the oldest methods adapted to many industrial areas to protect bioactive components. In this study, pH and heat tolerance of encapsulated probiotic Lactobacillus acidophilus NRRL B-4495 cells were investigated. Additionally, influence of process conditions including outlet temperature and pullulan concentration on spray drying process was observed. Scanning electron microscopy images showed that incorporation of pullulan higher than 2.0 % in wall matrix created huge amount of fibrous particles. Spherical microcapsules having smooth surface were formed with 2.0 % pullulan (WPI-pullulan4.5:1) formulation leading to an improvement of barrier properties of microcapsules. Moreover, incorporation of pullulan improved the survival rate to 94.21 % after spray drying. Results suggested that decreasing outlet temperature exhibited much higher cell survivals up to 92.68 %. However, between outlet temperatures, significant differences (p≤0.05) in moisture content and recovery of final product indicated that more effective encapsulation of L. acidophilus NRRL B-4495 cells was achieved at 50 °C. During spray drying, due to dehydration and high heat, cytoplasmic membrane of bacterial cells undergo damage and therefore, microencapsulation in WPI-pullulan blend by spray drying provided the highest survival against heat stress at 45 ºC. Moreover results showed that encapsulated cells survived at minimum desired level (7 log CFU/g) at pH 2.0 in contrast to free cells.